Unmodern men in the modern World - "Mazarr, Michael J." (Cambridge, 2007)
A sense of malaise and uncertainty surrounds the so-called war on terror. This volume offers a bold rethinking of the central challenge in that conflict: the rise of radical Islamism. Mazarr argues that this movement represents the latest in a series of anti-modern political and philosophical rebellions: in its causes, the shape of its ideology, and its social consequences, the movement shares much in common with German fascism, Russian revolutionary doctrines, and Japanese imperialist nationalism. The book builds a model of how anti-modern movements arise and suggests broader truths about the changing character of world politics and the psychological basis of national security in a globalized world. It concludes with a critique of the war on terror as currently pursued and a wide-ranging proposal for a strikingly different approach to the challenge of this latest challenge to modernity.
Keywords: Terrorism-United States-Prevention